Diseño del sistema de explotación de zeolita en la Concesión Minera Maival código 690726, parroquia El tablón, cantón Saraguro - Ordoñez Loja, Jhosty Enrique (2025)
The development of this research was carried out with the objective of designing an exploitation system for the mining concession "Maival", code 690726, located in the parish of El Tablón in the Saraguro canton. The disorganization of the workings and the antitechnical exploitation of the zeolitic mineral generated the need to design an exploitation system that is related to the conditions of the mineralized body according to technical, economic and environmental parameters. The research had as a starting point the delimitation of the study area together with its topographic survey and field sampling to analyze the quality of the zeolitic ore according to physical properties tests such as specific weight, porosity, moisture content, in addition to mineralogical and chemical tests such as x-ray diffraction and x-ray fluorescence, which allowed me to define the type of zeolite as a huelandite, clinoptilolite and barrerite, and the percentages of oxides present, which allowed me to define the silica/aluminum ratio. Following the geological characterization through the description of outcrops, calicatas and as a complement to know the depth to which the zeolitic mineral extends, 3 lines of vertical electrical soundings (SEV) were implemented that allowed reaching a depth of 23.72m and 20.70 in zeolitic breccia material and 30. 63 in felsic breccia material respectively, the zeolitic resources were calculated according to the profile methodology with a total of 2,480,959.99 Tn of exploitable material with a sterile amount of 91,331.41 Tn, giving an economic valuation to the deposit of 19,847,679.88 $. Subsequently, the exploitation system was chosen according to geotechnical, economic, technological and environmental parameters, defining a mixed exploitation system, the first two phases by quarrying and the two final phases by cutting, defining its geometric parameters according to the topography and conditions of the rock massif. An environmental management plan was implemented through the identification and valuation of impacts, defining compliance subprograms, finally an economic valuation of the exploitation system and mineral resources was made, defining it as profitable, covering operating and investment costs, with an NPV of less than 12% and a rate of return on investment at the beginning of the sixth year.